AVALIAÇÃO DAS EMISSÕES DE GASES DE EFEITO ESTUFA ATRAVÉS DA COMPARAÇÃO DOS MÉTODOS DE DESTINAÇÃO FINAL DE RESÍDUOS GERADOS NA ATIVIDADE DE PRODUÇÃO DE PETRÓLEO OFFSHORE - Pollis, Altaira Maia (2008)
This work aims to achieve a favorable environmental solution for the oil and gas industry waste management challenges. So, the study presents the green house gas (GHG) emissions analysis for two waste management alternatives. The study compares two different methods of final disposal: transport and final disposal at land versus waste incineration at the offshore facility, in order to establish the preferable method based on the environmental aspect. A case study is presented based on the evaluation of waste generation and management one year data of the oil and gas production activity at Bijupirá and Salema fields, located at Campos basin and operated by Shell Brasil. The GHG inventory was done based on the waste generation data and the final disposal technology used and the comparison with the GHG emitted if the same waste volume was incinerated at the offshore facility. Therefore, the study presents comparative analysis of the GEE emitted by the two alternatives, in order to identify which one provides the less GEE emissions and consequently the minimum environmental impact locally and globally.